Design and Development of Ti–Ni, Ni–Mn–Ga and Cu–Al–Ni-based Alloys with High and Low Temperature Shape Memory Effects - Pushin, Vladimir (Materials (Basel), 2019)
In recent years, multicomponent alloys with shape memory effects (SMEs), based on the ordered intermetallic compounds B2–TiNi, L2(1)–Ni(2)MnGa, B2– and D0(3)–Cu–Me (Me = Al, Ni, Zn), which represent a special important class of intelligent materials, have been of great interest. However, only a small number of known alloys with SMEs were found to have thermoelastic martensitic transformations (TMTs) at high temperatures. It is also found that most of the materials with TMTs and related SMEs do not have the necessary ductility and this is currently one of the main restrictions of their wide practical application. The aim of the present work is to design and develop multicomponent alloys with TMTs together with ways to improve their strength and ductile properties, using doping and advanced methods of thermal and thermomechanical treatments. The structure, phase composition, and TMTs were investigated by transmission- and scanning electron microscopy, as well as by neutron-, electron- and X-ray diffraction. Temperature measurements of the electrical resistance, magnetic susceptibility, as well as tests of the tensile mechanical properties and special characteristics of SMEs were also used. Temperature–concentration dependences for TMTs in the binary and ternary alloys of a number of quasi-binary systems were determined and discussed. It is shown that the ductility and strength of alloys required for the realization of SMEs can be achieved through optimal alloying, which excludes decomposition in the temperature range of SMEs’ usage, as well as via various treatments that ensure the formation of their fine- (FG) and ultra-fine-grained (UFG) structure.